Academy May Train A-Crews - Vallejo Times-Herald (Vallejo Times-Herald)
The Atomic Energy Commission has indicated it will consider using the California Maritime Academy and other state maritime academies to train crews for nuclear powered merchant ships when the demand for nuclear trained crews develops.